ChemInform Abstract: Ligand Modified CuFe2O4 Nanoparticles as Magnetically Recoverable and Reusable Catalyst for Azide‐Alkyne Click Condensation. Issue 18 (11th April 2013) - Ishikawa, Shingo; Hudson, Reuben; Moores, Audrey; Li, Chao‐Jun
Abstract This reaction does not require strict conditions such as anhydrous or degassed solvents or an inert atmosphere, and is applicable to gram scale synthesis.